1982
DOI: 10.1063/1.443323
|View full text |Cite
|
Sign up to set email alerts
|

The dielectric relaxation time of supercooled water

Abstract: The complex dielectric constant of liquid water was measured at 9.61 GHz down to −18 °C by means of a two resonant cavities apparatus. The static dielectric constant of bulk samples was also measured at 27.5 MHz down to −16.5 °C using a resonant circuit technique. From the analysis of the experimental results it follows that water in the metastable region has practically a single dielectric relaxation time τ. An analysis of the dynamic properties of water using our results and available data in literature, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(160 citation statements)
references
References 31 publications
11
146
0
3
Order By: Relevance
“…In other related work [21,48,49], such mid frequency relaxation behavior has been attributed to water absorbed at the nanoparticle interfaces. Compared to analogous silica-based systems [37,38], the major relaxation frequency here is much lower ~250 Hz, indicating a significantly reduced mobility of the water, as discussed in detail elsewhere [18][19][20][21].…”
Section: B Nanocomposite Dielectric Responsementioning
confidence: 97%
See 1 more Smart Citation
“…In other related work [21,48,49], such mid frequency relaxation behavior has been attributed to water absorbed at the nanoparticle interfaces. Compared to analogous silica-based systems [37,38], the major relaxation frequency here is much lower ~250 Hz, indicating a significantly reduced mobility of the water, as discussed in detail elsewhere [18][19][20][21].…”
Section: B Nanocomposite Dielectric Responsementioning
confidence: 97%
“…Comrie et al [19], for example, report a correlation between changes in the mechanical strength of adhesive joints and variation in the observed dielectric spectrum. Free, liquid water is characterized by a dielectric relaxation process at about 9.6 GHz [20], but the presence of local interactions can dramatically affect this. Lau et al [21] reported on the dielectric response of nanosilica/polyethylene systems and showed that water accumulates at nanofiller surfaces to an extend that is dependent upon the nanofiller surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Stogryn [13] used a fit based on the measurements of [29]. Both fits differ by less than 0.03% over the temperature range between C and C. They are also in excellent agreement with the measurements of [28] and the low temperature values of [33]. For reference, we use the fit given in [13] (7)…”
Section: A Two Debye Relaxation Fits For Pure Watermentioning
confidence: 99%
“…32,38 In particular, the peak ω max of the dielectric loss ′′-(ω) shifts to lower frequencies with cooling the solvent. The corresponding Debye relaxation time, τ D ) 1/ω max (diamonds in Figure 3), compares very well to the experimentally reported values 32,33 (closed diamonds and half-open triangles in Figure 3).…”
Section: S(t) )mentioning
confidence: 99%
“…32,38 In particular, the peak ω max of the dielectric loss ′′-(ω) shifts to lower frequencies with cooling the solvent. The corresponding Debye relaxation time, τ D ) 1/ω max (diamonds in Figure 3), compares very well to the experimentally reported values 32,33 (closed diamonds and half-open triangles in Figure 3). A similarly good agreement was reported previously by Rønne et al 33 for MD simulations in a narrower temperature range (271.5 e T e 368.15) on a smaller system (216 SPC/E molecules, 4 ns runs with the time step of 2 fs).…”
Section: S(t) )mentioning
confidence: 99%